EFEKTIVITAS PERAN KOMITE SEKOLAH DI SDIT IDRISIYYAH CIDAHU KECAMATAN CISAYONG KABUPATEN TASIKMALAYA - dina indriani; Utep Ahmad Zulfiqor; Emi Sriwahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research investigates the effectiveness of the School Committee's role at SDIT Idrisiyyah Cidahu in performing its functions. The School Committee plays a crucial role in supporting the improvement of educational quality through various functions: providing considerations, support, control, and mediation. However, the effectiveness of these roles often varies. This study aims to identify the extent to which the School Committee at SDIT Idrisiyyah Cidahu effectively carries out its functions. The research methodology employed a descriptive qualitative approach, utilizing interviews and observations as data collection techniques to gain an in-depth understanding of the activities and impact of the School Committee's role. The findings indicate that, out of the four primary functions of the School Committee, only the support and mediator functions are effectively implemented at SDIT Idrisiyyah Cidahu. The functions of providing considerations and control have not demonstrated optimal effectiveness, suggesting gaps in the committee's active participation in strategic decision-making and policy oversight. The significance of this research is highly relevant to the field of Islamic Education Management, as it offers insights into school governance dynamics and the potential for developing the School Committee's role to achieve better educational outcomes. These findings recommend the need to enhance the capacity and optimize the School Committee's role, particularly in the aspects of consideration and control, to foster a more comprehensive collaboration between the school and the community.